The Role of Information and Communiication Technology Combating Crime in Nigeria in The Post Covid 19 Era: A Study of the Nigeria Police Force, Lagos State Command - Osawe Cyril Onyepuemu; Ojo Ann David; Ashade Oladimeji Abiodun; Aliu Fatimo Ogechukwu (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2022)
The study seeks to examine the impact of Information and Communication Technology (ICT) on combating crime by the security forces in the wake of corona virus pandemic with special reference to the Nigeria Police Force (NPF). Within the framework of cybernetic theory, this study adopts the descriptive survey method to examine the relationship between the two variables under investigation. Multi stage sampling technique was used to draw a sample size of three hundred (300) participants for the study. Data were collected from the sampled population, and formulated hypotheses were tested using Pearson Product Moment Correlation Coefficient (PPMCC) statistical tool. The finding of the study reveals that there is a significant relationship between the use of ICT and the effort by the police force to effectively combat crime in Nigeria. The study also discovers that the use of ICT in the fight against crime by the NPF is faced with some challenges, which includes among others; lack of infrastructure, lack of adequate training, uncooperative attitude of ICT service providers and lack of inter-agency cooperation. The paper in conclusion, recommends that the NPF should improve on the usage of ICT especially during this post COVID-19 era by providing a robust training program for her personnel on the usage of ICT in combating crime, the government should provide adequate infrastructure to enhance effective application of ICT in crime fighting and an effective collaboration between ICT service providers and the NPF in fighting crime in Nigeria.